Digital Therapeutic Alliance With Fully Automated Mental Health Smartphone Apps: A Narrative Review - Tong, Fangziyun; Lederman, Reeva; D'Alfonso, Simon; Berry, Katherine; Bucci, Sandra (Frontiers in Psychiatry, 2022)
Fully automated mental health apps show strong promise in increasing access to psychological support. Therefore, it is crucial to understand how to make these apps effective. The therapeutic alliance (TA), or the relationship between healthcare professionals and clients, is considered fundamental to successful treatment outcomes in face-to-face therapy. Thus, understanding the TA in the context of fully automated apps would bring us insights in building effective apps which are able to engage users. However, the concept of a digital therapeutic alliance (DTA) in the context of fully automated mental health apps is nascent and under-researched, and only a handful of studies have been published in this area. In particular, no published review paper examined the DTA in the context of fully automated apps. The objective of this review was to integrate the extant literature to identify research gaps and future directions in the investigation of DTA in relation to fully automated mental health apps. Our findings suggest that the DTA in relation to fully automated apps needs to be conceptualized differently to traditional face-to-face TA. First, the role of bond in the context of fully automated apps is unclear. Second, human components of face-to-face TA, such as empathy, are hard to achieve in the digital context. Third, feelings or experiences, such as not being judged and flexibility, can be more easily derived from digital interventions compared to in-person therapy. Theories in Human-Computer Interaction, such as affective computing, positive computing, persuasive technology, and human-app attachment, can potentially help to foster a sense of empathy, build tasks and goals and develop bond or an attachment between users and apps, which may further contribute to DTA formation in fully automated apps. Whilst the review produced a relatively limited quantity of literature, this reflects the novelty of the topic and the need for further research.